2020
DOI: 10.1093/ajh/hpaa119
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability and Dementia: A State-of-the-Art Review

Abstract: Accumulating evidence demonstrates that blood pressure variability (BPV) may contribute to target organ damage, causing coronary heart disease, stroke, and renal disease independent of the level of BP. Several lines of evidence have also linked increased BPV to a higher risk of cognitive decline and incident dementia. The estimated number of dementia cases worldwide is nearly 50 million, and this number continues to grow with increasing life expectancy. Because there is no effective treatment to modify the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 98 publications
0
92
0
1
Order By: Relevance
“…In contrast, we found that elevated SBP was associated with a reduced risk of dementia in subjects without hypertension, heart disease, or cognitive impairment, compared with those having a normal SBP. This finding conflicted with the accumulated evidence that BP variation was positively associated with the risk of dementia regardless of the direction [ 8 11 ]. In a practical sense, SBP should not be elevated by intervention for the purpose to reduce the risk of dementia.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast, we found that elevated SBP was associated with a reduced risk of dementia in subjects without hypertension, heart disease, or cognitive impairment, compared with those having a normal SBP. This finding conflicted with the accumulated evidence that BP variation was positively associated with the risk of dementia regardless of the direction [ 8 11 ]. In a practical sense, SBP should not be elevated by intervention for the purpose to reduce the risk of dementia.…”
Section: Discussionmentioning
confidence: 62%
“…Blood pressure (BP) as one of the modifiable vascular factors was observed to be associated with dementia outcomes in various forms, such as mean measure [ 3 ], prehypertension [ 4 ], orthostatic hypotension [ 5 ], and pulse pressure (PP) [ 6 ]. Recently, accumulated evidence indicates that BP variability, which contributes to cerebrovascular damage as an independent factor of mean BP [ 7 ], is positively associated with the risk of dementia [ 2 , 8 11 ]. The possible mechanism may be that a higher BP variability is correlated with increased hyperintensity lesions of white matter on brain imaging [ 12 ], increased intima-media thickness of carotid artery [ 13 ], and accelerated progression of early carotid atherosclerosis [ 2 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the effect of elevated BP on cognitive decline appears to be mediated by both vascular pathology as well as neuritic plaques and neurofibrillary tangles, suggesting that managing BP can alleviate both vascular and neurodegenerative pathways [ 107 109 ]. Beyond elevated mean BP, fluctuations of BP over a period of hours, days and years have been increasingly found to influence brain health [ 110 , 111 ▪ , 112 ▪▪ ]. Emerging evidence suggests a link between BP variability, SVD progression and dementia risk [ 111 ▪ , 113 ].…”
Section: Management Of Vascular Cognitive Impairmentmentioning
confidence: 99%
“…Beyond elevated mean BP, fluctuations of BP over a period of hours, days and years have been increasingly found to influence brain health [ 110 , 111 ▪ , 112 ▪▪ ]. Emerging evidence suggests a link between BP variability, SVD progression and dementia risk [ 111 ▪ , 113 ]. More insights are needed to define this complex relationship between BP profile in ageing and cognitive impairment.…”
Section: Management Of Vascular Cognitive Impairmentmentioning
confidence: 99%
“…pdf dementia (Schneider et al, 2007), there is growing interest to study BPV in the context of cognitive aging and AD risk. Recent work suggests that elevated BPV is associated with cerebrovascular disease (Ma, et al, 2020a) and predictive of cognitive impairment and dementia, including AD and vascular dementia (Ma et al, 2020b;Rouch et al, 2020;Yoo et al, 2020), even in healthy older adults with wellcontrolled average BP (Cho et al, 2018). Chronic large fluctuations in BP may stress arterial walls and promote microvascular injury and arterial remodeling (Nagai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%